Błędy tłumaczeniowe i redakcyjne w wytycznych szkoleniowych dla sędziów koszykarskich w konfrontacji angielsko-polskiej - Sobczak, Michał; Pankanin, Emilia (Acta Neophilologica, 2019)
This paper examines the Polish translation of the Official Guidelines for Basketball Referees approved by the International Basketball Association (FIBA). It addresses the notion of specialist languages and indicates that the official guidelines for basketball referees possess some characteristics of a specialized text. Referring to translation competence, the article suggests that a non-professional translation of the guidelines can lead to their misinterpretation and, as a result, can influence the course of a game. The article concludes with implications for further theoretical and empirical research on the translation in question.